Targeting of antithrombin in hemophilia A or B with investigational siRNA therapeutic fitusiran—Results of the phase 1 inhibitor cohort. (18th May 2021) - Pasi, K. John; Lissitchkov, Toshko; Mamonov, Vasily; Mant, Tim; Timofeeva, Margarita; Bagot, Catherine; Chowdary, Pratima; Georgiev, Pencho; Gercheva‐Kyuchukova, Liana; Madigan, Kate; Van Nguyen, Huy; Yu, Qifeng; et al.
Abstract: Background: Fitusiran, an investigational small interfering RNA therapy, reduces antithrombin production to rebalance hemostasis in people with hemophilia A or B, with or without inhibitors. Objectives: To evaluate the safety and efficacy of fitusiran treatment for people with moderate/severe hemophilia A or B with inhibitors. Patients/Methods: In this open‐label phase 1, part D study, 17 males with hemophilia A or B with inhibitors received three once‐monthly subcutaneous injections of fitusiran 50 mg ( n  = 6) or 80 mg ( n  = 11); followed for up to 112 days. Endpoints included safety (primary), pharmacokinetics/pharmacodynamics (secondary), annualized bleeding rate, and patient‐reported outcomes (exploratory). Results: The most common adverse event was injection site erythema ( n  = 8). No thrombotic events were reported. At nadir, mean (standard error of the mean [SEM]) antithrombin activity decreased from baseline by 82.0% (2.2) and 87.4% (0.7) in the 50 mg and 80 mg groups, respectively. Antithrombin reduction was associated with increased thrombin generation. 11/17 (64.7%) participants had no bleeds during the observation period (mean [standard deviation] 69.4 [16.3] days). Mean (SEM) changes from baseline in Haemophilia Quality of Life Questionnaire for Adults total (−9.2 [2.9]) and physical health (−12.3 [3.9]) domain scores suggested clinically meaningful improvement. Conclusions: Monthly fitusiran was generally well tolerated, lowered antithrombin levels from baseline, and resulted in improved thrombin generation. These preliminary results suggest that monthly fitusiran treatment may reduce bleeding episodes and improve quality of life in participants with hemophilia A or B with inhibitors.